2017
DOI: 10.1161/circulationaha.116.023033
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Death in Contemporary Adult Patients With Eisenmenger Syndrome

Abstract: There is significant premature mortality among contemporary adults with Eisenmenger syndrome. We report, herewith, a multivariable mortality risk stratification model based on 5 simple, noninvasive predictors of death in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
6
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 29 publications
8
82
6
3
Order By: Relevance
“…As stated, underlying shunt was not found to be related to mortality in this study, which is in disagreement with Kempny et al , who on multivariable analysis, quoted a mortality HR of 1.56 for those with pretricuspid shunts (p=0.041) 12. This discrepancy between the two studies is difficult to reconcile given the low proportion of patients in the current study with pretricuspid lesions (10.7%) and the borderline significance of the association on multivariable analysis in the prior study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As stated, underlying shunt was not found to be related to mortality in this study, which is in disagreement with Kempny et al , who on multivariable analysis, quoted a mortality HR of 1.56 for those with pretricuspid shunts (p=0.041) 12. This discrepancy between the two studies is difficult to reconcile given the low proportion of patients in the current study with pretricuspid lesions (10.7%) and the borderline significance of the association on multivariable analysis in the prior study.…”
Section: Discussioncontrasting
confidence: 99%
“…Contemporary data in this regard are mixed, with two recent cohort studies also finding a survival benefit in those treated with AT 11 13. Conversely, a recently published multicentre study of >1000 patients with ES (62.8% on AT) did not find an association between survival and AT on multivariable analysis (though an association was shown in univariable analysis) 12. The reason for this discrepancy may be the relatively short follow-up time of approximately 3 years in the latter study.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A multidimensional approach should be considered. The five risk factors which predict poor outcomes in a previously published study include older age, presence of a pretricuspid shunt, reduced oxygen saturation at rest, the loss of of sinus rhythm and the presence of a pericardial effusion 4. This current study also showed the importance of age as well as potential benefits of AT.…”
Section: The Need For Risk Stratification To Focus Therapiessupporting
confidence: 67%
“…This appears to be a worldwide phenomenon even in populations with generally good access to adult congenital heart disease (ACHD) services. In one of the largest studies of 1089 patients, despite almost 50% of patients in functional class III, only about a third received AT 4. This current study by Arnott and colleagues should be congratulated as it represents the highest published proportion of patient treated to date with AT at up to 73%.…”
Section: Challenging the Notion That Es Is Not As Important As Idiopamentioning
confidence: 68%